Transcriptional regulation is insufficient to explain substrate‐induced flux changes in Bacillus subtilis. Issue 1 (26th November 2013) - Chubukov, Victor; Uhr, Markus; Le Chat, Ludovic; Kleijn, Roelco J; Jules, Matthieu; Link, Hannes; Aymerich, Stephane; Stelling, Jörg; Sauer, Uwe
Abstract : One of the key ways in which microbes are thought to regulate their metabolism is by modulating the availability of enzymes through transcriptional regulation. However, the limited success of efforts to manipulate metabolic fluxes by rewiring the transcriptional network has cast doubt on the idea that transcript abundance controls metabolic fluxes. In this study, we investigate control of metabolic flux in the model bacterium Bacillus subtilis by quantifying fluxes, transcripts, and metabolites in eight metabolic states enforced by different environmental conditions. We find that most enzymes whose flux switches between on and off states, such as those involved in substrate uptake, exhibit large corresponding transcriptional changes. However, for the majority of enzymes in central metabolism, enzyme concentrations were insufficient to explain the observed fluxes—only for a number of reactions in the tricarboxylic acid cycle were enzyme changes approximately proportional to flux changes. Surprisingly, substrate changes revealed by metabolomics were also insufficient to explain observed fluxes, leaving a large role for allosteric regulation and enzyme modification in the control of metabolic fluxes. Abstract : Regulation of enzyme expression is one key mechanism by which cells control their metabolic programs. In this work, a quantitative analysis of metabolism in a model bacterium under different conditions shows that expression alone cannot explain the majority of the observed metabolic changes. Synopsis: Regulation of enzyme expression is one key mechanism by which cells control their metabolic programs. In this work, a quantitative analysis of metabolism in a model bacterium under different conditions shows that expression alone cannot explain the majority of the observed metabolic changes. Most enzymes are indeed highly expressed in conditions where they are more active. Quantitatively, however, the observed changes in expression between conditions do not match the changes in activity for most enzymes. A good quantitative match is only observed for enzymes involved in the TCA cycle. Metabolomics reveals that increased substrate availability explains only a few instances of changes in activity.